Cymbella alexandrovichii sp. nov. (Cymbellaceae, Bacillariophyceae), a new cymbelloid diatom species with predominantly biseriate striae from South-East Asia - Glushchenko, Anton; Mironov, Andrei; Kuznetsova, Irina; Kulikovskiy, Maxim (Phytotaxa, 2023)
A new species from the genus Cymbella is described based on the morphological study using light and scanning electron microscopy. In the new species, striae are predominantly biseriate except for the central part of the valve, where they become uniseriate. Cymbella alexandrovichii sp. nov. is compared to 8 similar species of Cymbella that possess biseriate striae throughout the valve or only near the apices. Another species with biseriate striae—Gomphocymbellopsis guijiangensis—was included in the comparison based on the similar morphology. In addition, 3 species of Cymbella are compared to Cymbella alexandrovichii sp. nov. herein, despite lacking biseriate striation. The new species can be distinguished from similar taxa by a combination of features: asymmetric lanceolate outline with convex dorsal margin, not protracted cuneate to bluntly rounded valve ends, predominantly biseriate striae and 2–3 ventral stigmata.